An Axiological Perspective On Abortion Decisions: A Case Study Of Individuals' Reasons As A Reflection Of Values And Ethics - Windadari Murni Hartini; Suryo Ediyono (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Abortion, as an intentional act of terminating pregnancy, focuses on various reasons, including maternal health conditions, fetal abnormalities, pregnancies resulting from rape, and economic and social factors. Abortion is considered a significant public health issue, particularly due to its substantial impact on maternal morbidity and mortality. This study also highlights the importance of considering values and ethics in abortion decision-making, emphasizing the role of an axiological approach. The research method is qualitative with a phenomenological approach. The findings indicate that abortion decisions are influenced by economic factors, marital status, and psychosocial aspects. An axiological approach is crucial for considering ethical and moral values in abortion decisions.